Prevalência e fatores associados à enteroparasitoses em escolares - Monteiro, Ana Carolina da Silva (2017)
Intestinal parasites are recognized as a major public health problem in developing countries. Enteroparasites are neglected diseases or neglected tropical diseases because they correspond to a group of diseases that predominantly affect the poorest and most vulnerable populations, contributing to the cycle of poverty, inequality and social exclusion. In Brazil the enteroparasitoses are still very widespread and with high prevalence, mainly in the Northeast region. The prevalence of enteroparasitoses in school-aged children is higher due to their inadequate hygiene habits, causing an outbreak of enteroparasitosis culminating for pathological effects in their host in relation to malnutrition, anemia, diarrhea, school use and nutritional deficit. The present study aims to determine the prevalence of enteroparasitoses in school - aged children, as well as to establish a relationship between the results to be obtained and the socioeconomic, health and nutritional conditions in these children. It is an observational study with a cross-sectional design and descriptive analysis, carried out with a sample of 150 children who study at the Lions Tambaú Elementary School, in the city of João Pessoa - PB. The logistic regression model was used to explain the occurrence of enteroparasitoses and to subsidize decision making based on the socioeconomic, nutritional and health variables of the children collected in the study. The prevalence of enteroparasitosis was 38.7%, children with a positive sample of these were more prevalent in male children (47.0%). The most prevalent enteroparasites were enterocomial protozoa, which presented 63.6%, which are related to the consumption of contaminated water, as well as the lack of hygiene of the people. The variables that presented statistical significance (p-value <0.05) were: gender (OR = 0.42), receive family allowance (OR = 4.42), number of rooms in the residence (OR = 3.46), (OR = 4.25), fruit and vegetable hygiene (OR = 2.03), walks barefoot (OR = 6.98), use of vermifuge for human (OR = 0.02) and visualization of Worms (OR = 24.9). The occurrence of these data reinforces the need to implement preventive measures of a theoretical and practical nature, such as health education, in order to demonstrate the damage of parasitic diseases through hygiene, basic sanitation, prevention and recognition of signs and symptoms indicative of Enteroparasitoses.